LOAD ANALYSIS OF A MULTI-MOTOR PROPULSION SYSTEM (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2026)
Managing load from multiple electric motors integrated into a vehicle's propulsion system is a complex problem, primarily involving vehicle stability, particularly when the motors are distributed independently across vehicle axles or wheels. The management of each motor's participation in achieving the traction torque, on the other hand, improves energy efficiency and performance. It is necessary to manage each motor's behavior across the entire operational range, as this contributes to the energy efficiency of the electric powertrain. In this context, the paper aims to present a synthesis of research conducted by the author in this field.
Keywords: EV (electric vehicle); Multi-motor; Torque transfer; Simulation; Efficiency maps; Methods for charging a multi-motor system